Flavonoid synergy in antioxidant optimization: a study of Apium graveolens and Orthosipon stamineus - Astuti, Febriana; Akrom; Setianto, Arif Budi; Hidayati, Titiek; Mustofa; Anwar, Muslih; Sun, Suny (Pharmaciana, 2025)
Oxidative stress, which arises by an imbalance among the formation of free radicals and the body's antioxidant defenses, is a pivotal factor in the pathogenesis of numerous degenerative abnormalities, comprising cardiovascular abnormality. Flavonoids, that are natural chemicals by antioxidant capabilities, have been identified as potential agents for protection against the adverse impacts of oxidative stress. The objective of this study was to ascertain the flavonoid substance of Apium graveolens and Orthosipon stamineus extracts and their antioxidant activity. The technique comprising qualitative and quantitative phytochemical tests to decide the flavonoid substance of the extracts. In addition, bioactive compounds were screened utilizing LC-HRMS, and antioxidant activity was evaluated utilizing the DPPH technique. The outcomes of this study drawn the presence of flavonoid compounds, alkaloids, tannins, and saponins in the Apium graveolens and Orthosipon stamineus extracts. The Orthosipon stamineus extract was found to contain steroid compounds. The screening of flavonoids compounds utilizing LC-HRMS has drawn the presence of the greatest diversity of flavonoid compounds in the Apium graveolens extract. The antioxidant activity assay employed quercetin as the standard, possessing an IC₅₀ value of 3.95 μg/mL. Apium graveolens extract exhibited an IC₅₀ value of 58.86±0.44μg/mL, Orthosiphon stamineus extract drawn an IC₅₀ value of 61.69±0.21 μg/mL, whereas the combined extract yielded an IC₅₀ value of 46.32±0.34 μg/mL. The outcomes indicate that the extract combination shows superior free radical scavenging ability compared to the individual extracts, suggesting its potential to enhance the antioxidant efficacy of bioactive compounds derived by herbal plants.